[11C](R)-Rolipram positron emission tomography detects DISC1 inhibition of phosphodiesterase type 4 in live Disc1 locus-impaired mice. Issue 7 (July 2019) - Ooms, Maarten; Tsujikawa, Tetsuya; Lohith, Talakad G; Mabins, Sanché N; Zoghbi, Sami S; Sumitomo, Akiko; Jaaro-Peled, Hanna; Kimura, Yasuyuki; Telu, Sanjay; Pike, Victor W; Tomoda, Toshifumi; Innis, Robert B; et al.
Although still a matter of controversy, disrupted in schizophrenia protein 1 (DISC1) was suggested as a potential inhibitor of phosphodiesterase 4 (PDE4). We used Disc1 locus impairment (LI) mice to investigate the interaction between PDE4 and DISC 1 in vivo and in vitro . [ 11 C]( R )-Rolipram binding was measured by PET in LI ( n  = 11) and C57BL/6 wild-type (WT, n  = 9) mice. [ 11 C]( R )-Rolipram total distribution volumes ( V T ) were calculated and corrected for plasma-free fraction ( f P ) measured in a separate group of LI ( n  = 6) and WT ( n  = 7) mice. PDE4 enzyme activity was measured using in vitro samples of cerebral cortices from groups of LI ( n  = 4), heterozygote ( n  = 4), and WT ( n  = 4) mice. Disc1 LI mice showed a 41% increase in V T (18 ± 6 vs. 13±4 mL/cm 3, P  = 0.04) compared to WT mice. V T / f P showed a 73% significant increase (90 ± 31 vs. 52 ± 15 mL/cm 3, P  = 0.004) in Disc1 LI compared to WT mice. PDE4 enzymatic activity assay confirmed in vivo findings showing significant group differences ( p  < 0.0001). In conclusion, PDE4 activity was increased in the absence of critical DISC1 protein isoforms both in vivo and in vitro. Additionally, [ 11 C]( R )-Rolipram PET was sensitive enough to assess altered PDE4 activity caused by PDE4–DISC1 interaction.